COMPARE Family (Children of Mentally Ill Parents at Risk Evaluation): A Study Protocol for a Preventive Intervention for Children of Mentally Ill Parents (Triple P, Evidence-Based Program That Enhances Parentings Skills, in Addition to Gold-Standard CBT With the Mentally Ill Parent) in a Multicenter RCT—Part II - Stracke, Markus; Gilbert, Kristin; Kieser, Meinhard; Klose, Christina; Krisam, Johannes; Ebert, David D.; Buntrock, Claudia; Christiansen, Hanna (Frontiers in Psychiatry, 2019)
Background: Mental health problems are highly frequent, as well as being associated with enormous societal and economic costs and significant disability-adjusted life years. Children of parents with a mental illness (COPMI) are at a tremendously increased risk to develop disorders themselves. According to the literature, parental mental disorders launch a wave of risk factors that in turn predict the emergence of psychological problems in the offspring, and effective treatment of the parental disorder has been associated with reduced child psychopathology (launch and grow assumption). Furthermore, studies focusing on parent-child interaction demonstrate generally poorer parenting skills in parents with mental disorders, and the enhancement of such skills has been a significant mediator in improving child outcomes (parenting assumption). Objective: To implement a preventive intervention for COPMI with the aim of interrupting the transmission of mental disorders in children of a parent with mental disorders. An RCT will compare state-of-the-art cognitive behavioral therapy (CBT) for a parent with mental disorders to CBT plus the Positive Parenting Program (Triple-P), a well-established and evidence-based program that enhances parenting skills. Methods: A total of 634 patients seeking treatment in 8 outpatient clinics in Germany and their children will be included between January 2018 and April 2021 in the study. We use (clinical) interviews and self- as well as other-report questionnaires to assess the families at four main measurement points [T1: beginning of waiting period for psychotherapy treatment (duration of waiting period depends on usual waiting period in the study center: multiple baselines), T2: begin of parental psychotherapy, T3: post-assessment, T4: 6 months follow-up]. The total observation period will be 39 months. The patients will be randomly assigned to either the control condition (25 to 45 CBT sessions) or the experimental condition (25 to 45 CBT sessions + 10 Triple-P sessions). For evaluating the treatment process, the patients and clinicians will also be assessed after each treatment session. Furthermore, there will be a continuous assessment and report of adverse events during treatment. Discussion: This trial will be the first ever to address the launch and grow as well as the parenting assumption in one study and to establish effects of the two different interventions on children's health. Our study will also likely be the first one to provide data on the comparative cost-effectiveness and will therefore provide essential information relevant for the potential implementation of such programs. The structure of the RCT will allow us to establish effects of the parental disorder(s) with/without comorbidities on children's health, to test assumptions of the trans-generational transmission model of mental disorders and bi-directional influences of different treatments on the model and to analyze specific transmission mechanisms. A deeper understanding of risk mechanisms will reveal specific transmission profiles that will result in the early detection of and effective reduction in risk factors and thus improve the health of the children at risk. Ethics: The study is carried out according to the Good Clinical Practice (GCP) guidelines, the Declaration of Helsinki and its later supplements and local legal requirements. The lead ethics committee at the department of psychology at Philipps-University Marburg approved the study procedure and all study documents. A positive ethics committee vote is required at a study site, before the inclusion of a first patient at the respective site. Dissemination: Via peer-reviewed publications in scientific journals, the results of this study will be made available to the scientific community. Using PsychData all primary data will be made available for re- and meta-analyses. Politicians, public health services, and stakeholders will be informed throughout the study and beyond, thus, improving public policy and health care decisions concerning preventive interventions and treatments for COPMI. Trial Registration: DRKS-ID: DRKS00013516 (German Clinical Trials Register, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00013516)